Functional state of the circulatory and respiratory systems in highly qualified athletes when using hyperbaric oxygenation in training conditions in the middle mountain region - Ter-Akopov, G. N.; Koryagina, Yu. V.; Kushnareva, Yu. V.; Nopin, S. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study of the dynamics of the functional state of the circulatory and respiratory systems in highly qualified athletes using HBOT in training conditions in mid-mountains.